Collaborative performance management for public health : a practical guide - McCarty, Amanda E.; Armbruster, Sonja M.; Moran, John W., 1944- (New York, NY : Routledge, 2020)
"Performance management can be an uncomfortable topic within the discipline of public health. Written by leaders in public health performance management and quality improvement, this book carefully explains what public health performance management is -- and makes a strong case for why it is needed to tackle successfully the long-standing health issues plaguing communities and states. Notably, the book eschews the need to invest in technology or to learn a new performance management vocabulary. Rather the authors advocate for more thoughtful use of the resources already available in the organization, relying on public health leadership working in conjunction with well trained staff to manage their own organizational performance. To be broadly accepted within public health, performance management concepts and models have to be framed and populated with public health examples, and this book offers a wealth of practical insights and case studies that may be immediately applied to public health organizations, from assessing an organization's needs, introducing a performance management system to the organization, developing an agency's goals and targets, to implementation of sound performance management systems and plans. Collaborative Performance Management for Public Health is required reading for all public health leaders and employees concerned with maximizing the health impact of scarce resources"--
Performance management in public health -- What is a performance management system? -- Introducing performance management to an organization -- The five stages of performance management -- Developing agency & programmatic goals, objectives, measures & targets -- Implementation & maintenance of a performance management system -- Developing a performance management plan -- Performance management case studies.
OCLC-licensed vendor bibliographic record.
Keywords: Public health -- United States -- Management; Health planning -- United States; Public health administration -- United States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / General